Regeneration of Jatiduwur Mask Puppet Performance Artists at the Tri Purwo Budoyo Studio, Kesamben, Jombang.: Regeneration of Jatiduwur Mask Puppet Performance Artists at the Tri Purwo Budoyo Studio, Kesamben, Jombang. - Puwargati, Arina Rimba; Yanuartuti, Setyo (Solah, 2025)
Wayang Topeng Jatiduwur is one of the traditional performing arts with high historical and aesthetic value in East Java. The continuity of this art form is highly dependent on the success of its practitioners’ regeneration. This study aims to examine the process of regenerating art practitioners at Sanggar Tri Purwo Budoyo, Kesamben, Jombang. Using a qualitative descriptive method, data was collected through observation, interviews, and documentation. Data validity was ensured through triangulation, while data analysis included reduction, presentation, and drawing conclusions. The results of the study indicate that the transmission of the Wayang Topeng Jatiduwur performance has undergone various eras, thereby the regeneration process has experienced vertical, horizontal, and diagonal transmission processes. These findings suggest that Sanggar Tri Purwo Budoyo applies an adaptive and contextual cultural preservation model.